2017
DOI: 10.1038/s41598-017-05184-5
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Microfluidic Production of Drug-Loaded PLGA Nanoparticles Using Partially Water-Miscible Mixed Solvent Microdroplets as a Precursor

Abstract: We present a versatile continuous microfluidic flow-focusing method for the production of Doxorubicin (DOX) or Tamoxifen (TAM)-loaded poly(D,L-lactic-co-glycolic acid) (PLGA) nanoparticles (NPs). We use a partially water-miscible solvent mixture (dimethyl sulfoxide DMSO+ dichloromethane DCM) as precursor drug/polymer solution for NPs nucleation. We extrude this partially water-miscible solution into an aqueous medium and synthesized uniform PLGA NPs with higher drug loading ability and longer sustained-release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 43 publications
6
86
0
Order By: Relevance
“…Despite these advantages, limitations such as high batch-to-batch variations, non-homogenous reaction environment 27 and insufficient production rate reveal the need to move towards techniques providing a higher control in the production of nanosystems with well-defined features.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advantages, limitations such as high batch-to-batch variations, non-homogenous reaction environment 27 and insufficient production rate reveal the need to move towards techniques providing a higher control in the production of nanosystems with well-defined features.…”
mentioning
confidence: 99%
“…One of the first examples is presented by Karnik and co-workers 43 , who produced PLGA-PEG nanoparticles, studying the effect of the flow-rate ratio on particle size and polydispersity by micellization. Recently, Xu et al, proposed a continuous flow focusing-based strategy to improve the encapsulation efficiency (EE%) of Tamoxifen and Doxorubicin, a hydrophobic and a hydrophilic anticancer drug respectively, in PLGA NPs 27 . In this work, they demonstrated that an improved EE% translates into a more controlled drug release.…”
mentioning
confidence: 99%
“…A continuous microfluidic flow-focusing method has also been engineered, providing a rapid, efficient, and low-cost formulation of hydrophobic molecules (e.g. tamoxifen) with high encapsulation efficiency [15]. Moreover, microfluidic systems have also been used for the formulation of nanoparticles (e.g.…”
Section: Microfluidicsmentioning
confidence: 99%
“…Droplet microfluidics involves sample partitioning into nanoliter or smaller volumes and has been extensively used in a variety of fields including biology, medicine, chemistry and physics [1][2][3][4]. Most commonly, aqueous fluids are encapsulated into droplets surrounded by a continuous phase of an oil surfactant mixture.…”
Section: Introductionmentioning
confidence: 99%